Cross-sectional returns with volatility regimes from a diverse portfolio of emerging and developed equity indices - Paweł Sakowski; Robert Ślepaczuk; Mateusz Wywiał (e-Finanse: Financial Internet Quarterly, 2016)
This article aims to extend evaluation of the classic multifactor model of Carhart (1997) for the case of global equity indices and to expand analysis performed in Sakowski et. al. (2015). Our intention is to test several modifications of these models to take into account different dynamics of equity excess returns between emerging and developed equity indices. Proposed extensions include a volatility regime switching mechanism (using dummy variables and the Markov approach) and the fifth risk factor based on realized volatility of index returns. Moreover, instead of using data for stocks of a particular market (which is a common approach in the literature), we check performance of these models for weekly data of 81 world investable equity indices in the period of 2000-2015. Such an approach is proposed to estimate an equity risk premium for a single country. Empirical evidence reveals important differences between results for classical models estimated on single stocks (either in international or US-only frameworks) and models evaluated for equity indices. Additionally, we observe substantial discrepancies between results for developed countries and emerging markets. Finally, using weekly data for the last 15 years we illustrate the importance of model risk and data overfitting effects when drawing conclusions upon results of multifactor models.
Keywords: C15; G11; F30; G12; G13; G14; G15; 330; cross-sectional models; asset pricing models; equity risk premiums; emerging and developed equity indices; data overfitting and model